2022
DOI: 10.33122/ijtmer.v5i3.122
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning Think Talk Write model with Powerpoint assistance on students' mathematics learning outcomes

Abstract: This study aims to know the effect of the Powerpoint-assisted Think Talk Write (TTW) learning model on student learning outcomes. The type of study is experimental and the design is one group pretest-posttest design. This type begins with measuring the initial ability of students than giving treatment and then giving a remeasurement or posttest. This analysis was conducted to determine the effect of the Powerpoint-assisted TTW learning model on students learning outcomes. The results of the study showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The results showed that the use of the jigsaw cooperative learning model can increase student interest and learning outcomes in the two-variable system of linear equations subject. This increase in learning interest can be seen from the average percentage of class interest, which is 37.7% before the action is carried out with the criteria for a low level of success, but after the action is carried out the percentage of interest (Muis & Priawasana, 2022;Nurhayati et al, 2018) learn experienced an increase in both cycle I and cycle II. The percentage of the results of filling out the questionnaire in the first cycle reached 64.0% with a good level of success criteria, then the percentage of completing the questionnaire in the second cycle reached 84.3% with very good success criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the use of the jigsaw cooperative learning model can increase student interest and learning outcomes in the two-variable system of linear equations subject. This increase in learning interest can be seen from the average percentage of class interest, which is 37.7% before the action is carried out with the criteria for a low level of success, but after the action is carried out the percentage of interest (Muis & Priawasana, 2022;Nurhayati et al, 2018) learn experienced an increase in both cycle I and cycle II. The percentage of the results of filling out the questionnaire in the first cycle reached 64.0% with a good level of success criteria, then the percentage of completing the questionnaire in the second cycle reached 84.3% with very good success criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Each type of cooperative learning model has specific stages and has a major difference, namely the existence of cooperation between group members. (Fitriah, Degeng, & Widiati, 2018;Muis & Priawasana, 2022) The Jigsaw cooperative learning model has its own advantages and characteristics so it is very affective when applied in the learning process. Jigsaw is cooperative learning which consists of 4 to 6 students with heterogeneous characteristics.…”
Section: Introductionmentioning
confidence: 99%